The old second messenger cAMP teams up with novel cell death mechanisms: potential translational therapeutical benefit for Alzheimer’s disease and Parkinson’s disease - Zhang, Tong; Luu, Minh D. A.; Dolga, Amalia M.; Eisel, Ulrich L. M.; Schmidt, Martina (Frontiers in Physiology, 2023)
Alzheimer's disease (AD) and Parkinson's disease (PD) represent the most prevalent neurodegenerative disorders severely impacting life expectancy and quality of life of millions of people worldwide. AD and PD exhibit both a very distinct pathophysiological disease pattern. Intriguingly, recent research, however, implicate that overlapping mechanisms may underlie AD and PD. In AD and PD, novel cell death mechanisms, encompassing parthanatos, netosis, lysosome-dependent cell death, senescence and ferroptosis, apparently rely on the production of reactive oxygen species, and seem to be modulated by the well-known, "old" second messenger cAMP. Signaling of cAMP via PKA and Epac promotes parthanatos and induces lysosomal cell death, while signaling of CAMP via PKA inhibits netosis and cellular senescence. Additionally, PKA protects against ferroptosis, whereas Epac1 promotes ferroptosis. Here we review the most recent insights into the overlapping mechanisms between AD and PD, with a special focus on cAMP signaling and the pharmacology of cAMP signaling pathways.